Pere Vicent Sabata, autor anònim: sobre els goigs del Ms. 804 de la BHUV. - CLIMENT, JOAN MAHIQUES (Scripta, 2024)
The Ms. 804 of the Biblioteca Històrica of the University of Valencia is a miscellany volume of "goigs" (popular religious songs) printed, for the most part, in Spanish as broadsides dated from the 18th century, explicitly or not. This paper begins with an overview of the content and characteristics of this volume. Then it focuses on a few handwritten "goigs" attributed to Pere Vicent Sabata which have been preserved in the Ms. 804 or in the Ms. 3619 of the Biblioteca de Catalunya. Finally, three more poems -two of them printed- are attributed to him through an analysis of the style and intertextual relationships. Until now any of them had never been attributed to Pere Vicent Sabata. This paper concludes with the transcription of eight "goigs" written or attributed to the aforementioned author.